Parental knowledge, attitude and practice related to blindness of children in some selected Upazilla of Bangladesh. (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):671-9 The abstract of this article is available on the PubMed website